PERANCANGAN NOVEL GRAFIS “PARARATON" YANG DIADAPTASI DARI KISAH KEN AROK - Jazuli Abdin Munib; Andi Cahyo Widiatmoko (TANRA: Jurnal Desain Komunikasi Visual Fakultas Seni dan Desain Universitas Negeri Makassar, 2022)
The project entitled Designing Graphic Novel of “PARARATON” through  Visual  Communication  Design with problem  studied is  how  to  design Graphic Novel of “PARARATON” creative, effective in order to be accepted by young people in particular and the general public. The main purpose of the design of this novel is to introduce Ken Arok’s life history before and after he became the king of Singasari. Therefore needed to design appearance and layout of the contents of novel that can be targeted to foster a sense of pride in young children to know one of folklore in Indonesia. People should know the life background of Ken Arok before and after he became the king of Singasari. It is importantant because Ken Arok was one of known folklore in Indonesia that must be preserved.